Creativity and Impact of Advertising Electronic Led Billboards in Jakarta - Suprayitno, Suprayitno (Bina Nusantara University, 2016)
The creativity and the impact of advertising electronic LED billboards in Jakarta was an approach to see, to know and to understand in a deeper way. Creativity decisions affect all advertising, art, and knowledge combined with the phrase creative strategy. Creative advertising ideas must be original, unique, different, new, unexpected and right on target. The approach used was qualitative research methods, including data collection in the form of literature review, interviews with the actors and the surrounding communities, as well as documenting the billboard directly outside the media was located. The results of this research are the analysis report the creativity and impact of LED electronic billboard advertising effectiveness, is expected to produce a more detailed picture. So that students and practitioners can use the visual communication design, process, and maximize the advertising rules in designing a design to reach the stage of design creativity and better application.